1998
DOI: 10.1103/physrevlett.81.1805
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and Transverse Cross Sections in the1H(e,e<

Abstract: The 1 H͑e, e 0 K 1 ͒L reaction was studied as a function of the squared four-momentum transfer, Q 2 , and the virtual photon polarization,´. For each of four Q 2 settings, 0.52, 0.75, 1.00, and 2.00 ͑GeV͞c͒ 2 , the longitudinal and transverse virtual photon cross sections were extracted in measurements at three virtual photon polarizations. The Q 2 dependence of the s L ͞s T ratio differs significantly from current theoretical predictions. This, combined with the precision of the measurement, implies a need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…More than a decade ago, Niculescu et al [68] have measured the e + p → e ′ + K + + Λ process and found that the longitudinal cross section dσ L /dΩ at Q 2 = 0.52 GeV 2 is significantly large, almost as large as the transverse one dσ T /dΩ. In order to reproduce these data an isobar model must dramatically increases both cross sections from photon point up to a certain value of Q 2 (see Fig.…”
Section: New Mami Data At Low Qmentioning
confidence: 99%
“…More than a decade ago, Niculescu et al [68] have measured the e + p → e ′ + K + + Λ process and found that the longitudinal cross section dσ L /dΩ at Q 2 = 0.52 GeV 2 is significantly large, almost as large as the transverse one dσ T /dΩ. In order to reproduce these data an isobar model must dramatically increases both cross sections from photon point up to a certain value of Q 2 (see Fig.…”
Section: New Mami Data At Low Qmentioning
confidence: 99%
“…Q 2 dependence of σT and σL (upper plot) and σL/σT (lower plot) for the γ * + p → K + + Λ reaction, at W = 1.84 GeV. Experimental data points are from : (•, •, ⋆) : [6] and (△) : [7]. Besides our calculation, on the lower panel are also shown the models of Ref.…”
mentioning
confidence: 90%
“…The signs of the K * strong coupling constants are also in accordance with SU(3). It turns out that the recent measurement [6], at Jefferson Lab, of the ratio between the Coulomb (σ L ) and the transverse (σ T ) cross-sections of the p(e, e ′ K + )Λ reaction clearly favors the Regge model over the resonance models, already in the CEBAF energy range. Fig.…”
mentioning
confidence: 99%
“…Most of the recent data has been obtained at Jefferson Lab, either by the Hall C Collaboration [33] or by CLAS [34][35][36]. The earliest theoretical studies of electroproduction date from the mid 1970s, and were based on a simple Regge model [37].…”
Section: Introductionmentioning
confidence: 99%